Efektifitas Media Promosi Kesehatan Audio Visual Lagu Cuci Tangan Terhadap Pelaksanaan Cuci Tangan 6 Langkah Pada Anak - Criony, James (Journal of Public Health Education, 2022)
Introduction: Hand washing is one of the personal hygiene steps taken to prevent disease. According to WHO, only 33.7% of children in the world have the habit of washing their hands, while according to the Indonesian Ministry of Health in 2016 there are only about 17% of Indonesian children behaved properly and properly. One of the efforts that can be done to overcome these problems is by promoting the health of audio-visual media. Objectives: This study aims to determine the effectiveness of audio-visual health promotion media using the song let's wash hands on the implementation of 6 steps of handwashing in children. Method: This study uses a quasi-experimental method with a one-group pretest-posttest design. The sample in this study was 30 children aged 8-10 years in Cilodong District. Result: The results of the sample paired t-test with a correlation value of 0.000 < 0.005, the average value of the pretest and posttest of 30 respondents is -15,667 and 66,67 this value shows the difference between before the respondent is given treatment and after the respondent is given treatment. The difference is between -18.87183 to -12.46150. Conclusion: There is an effect of health promotion on audio-visual media, let's wash hands on the implementation of the 6 steps of washing hands in children. Based on these results, it is known that the audio-visual media of the song let's wash hands is effective in increasing children's abilities in implementing the 6 steps of good and correct hand washing.